Demythization of the socialist ideal in Jedlička's prose Midway upon the journey of our life - Řezáčová, Meda Bára (Bohemica Olomucensia, 2020)
The analysis focuses on the relation between the compositional and shaping processes of Jedlička's prose and their function to reflect and deconstruct the socialist ideal. It does not seek to uncover detailed intertext links, but instead the analysis concentrates on Jedlička's ideal and idyllic thematic. The analysis uses Macura's concept of the socialist ideal and Bachtin's idyllic chronotope in relation to the character of the text as "witness testimony about the period."
Keywords: idyll; myth; Josef Jedlička; socialist ideal; Kde život náš je v půli se svou poutí; demythization; deconstruction